2002
DOI: 10.1161/hq0102.102189
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Nox-Based NAD(P)H Oxidases in Restenosis After Carotid Injury

Abstract: Abstract-Restenosis, a frequent complication of coronary angioplasty, is associated with increased superoxide (O 2 · Ϫ ) production. Although the molecular identity of the responsible oxidase is unclear, an NAD(P)H oxidase appears to be involved. In smooth muscle, p22phox and 2 homologues of gp91phox, nox1 and nox4, are expressed, whereas fibroblasts contain gp91phox. To begin investigating the possibility that these oxidase components might contribute to the increased O 2 · Ϫ that accompanies neointimal forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
322
5
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(358 citation statements)
references
References 45 publications
23
322
5
8
Order By: Relevance
“…Oscillatory sheer stress is associated with induction of bone morphogenic protein 4 (BMP4) [82], which induces Nox1 and p47phox, resulting in an oxidative stress that leads to ICAM-1 expression and monocyte adhesion [81]. Nox1 expression increases ~3-fold following balloon injury and precedes restenosis and atherosclerosis [83]. This in turn led to monocyte infiltration and a vicious cycle of increasing oxidant stress.…”
Section: Nox Enzymes and Atherosclerosismentioning
confidence: 99%
“…Oscillatory sheer stress is associated with induction of bone morphogenic protein 4 (BMP4) [82], which induces Nox1 and p47phox, resulting in an oxidative stress that leads to ICAM-1 expression and monocyte adhesion [81]. Nox1 expression increases ~3-fold following balloon injury and precedes restenosis and atherosclerosis [83]. This in turn led to monocyte infiltration and a vicious cycle of increasing oxidant stress.…”
Section: Nox Enzymes and Atherosclerosismentioning
confidence: 99%
“…ECs produce ROS and RNS from the enzymes and ·NO synthase and by specific homologues of NADPH oxidase (gp91 phox , Nox1, and Nox4) [41]. We previously demonstrated that NADPH oxidases were capable of producing high levels of ROS in blood vessels in response to specific stimuli arising from flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Using the balloon injury model in the rat, Griendling and colleagues observed that Nox1 as well as p22phox mRNA was upregulated 3 days post injury and sustained through 15 days post injury while there was an increase in gp91phox at 7 days post injury which also sustained through 15 days [149]. In addition Nox4 mRNA remained unchanged until 15 days post injury where an increase in the mRNA was observed.…”
Section: Nadph Oxidase Expression and Function In Vascular Injurymentioning
confidence: 99%
“…The same authors used immunohistochemistry to confirm that p22phox expression was detected basally in the adventitia of the vessel, but appeared in the medial smooth muscle layer by 7 days post injury and then most abundantly in the neointima by 10 days post injury, where Nox4 was only detected in medial and neointimal cells. However, they were not able to establish the site of Nox1 expression [149]. Moe et al investigated Nox expression in human aortic smooth muscle cells in response to the pro-inflammatory cytokine TNF-α.…”
Section: Nadph Oxidase Expression and Function In Vascular Injurymentioning
confidence: 99%